THE STUDY IMPACT OF WHATSAPP GROUP ON CRITICAL READING SKILL - Ranta Butarbutar (MAGISTRA, 2019)
WhatsApp group as a social media application has a great impact to improve the skills of students in critical reading particularly. This study aims to look at the impacts of group WhatsApp application in critical reading. The descriptive qualitative used as method to process the data. The participants were students majoring in English education semester totaling 30 peopleAbstrakWhatsApp group as a social media application has a great impact to improve the skills of students in critical reading particularly. This study aims to look at the impacts of group WhatsApp application in critical reading. The descriptive qualitative used as method to process the data. The participants were students majoring in English education semester totaling 30 people Kata Kunci: WhatsApp group; improving; critical reading